Consciência fonológica como uma habilidade metalinguística facilitadora da alfabetização: um estudo com alunos do 2º ano do Ensino Fundamental - Cruz, Simone Maria Martins (2021)
Currently, the scientific literature points to a strong relevance of metalinguistic skills for learning to read and write, of which phonological awareness is one of the fundamental metalinguistic skills for its development. This research aimed to analyze the relationship between the dependent variables (reading and writing) and the independent variables of phonological awareness (rhymes, syllabic segmentation, phonemic awareness). Twenty children, attending the 2nd year of Elementary School I in a municipal school of the City of São Paulo, participated in the research. For the study, an assessment of the phonological awareness skill was performed along with reading and writing. Students were assessed by a set of phonological awareness tasks as well as reading and writing of words. The analysis was performed using the Pearson´s correlation test. The results showed a positive correlation between metalinguistic ability (phonological awareness) and reading and writing skills